2019
DOI: 10.1051/0004-6361/201935862
|View full text |Cite
|
Sign up to set email alerts
|

Sunyaev-Zel’dovich detection of the galaxy cluster Cl J1449+0856 at z = 1.99: The pressure profile in uv space

Abstract: We present Atacama Large Millimetre Array and Atacama Compact Array observations of the Sunyaev-Zel'dovich effect in the z = 2 galaxy cluster Cl J1449+0856, an X-ray-detected progenitor of typical massive clusters in the present day Universe. While in a cleaned but otherwise untouched 92 GHz map of this cluster, little to no negative signal is visible, careful subtraction of known sub-millimetre emitters in the uv plane reveals a decrement at 5σ significance. The total signal is −190±36 µJy, with a peak offset… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 59 publications
1
24
0
Order By: Relevance
“…HST/WFC3 colour composite image of CL J1449+0856. The grey dashed contours represent the X-ray intensity map from Chandra (Valentino et al 2016), while the extended green contours display the SZ signal tracing the mass distribution (Gobat et al 2019). The cyan contours are the 870 μm ALMA sources.…”
Section: Data O B S E Rvat I O N a N D R E D U C T I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…HST/WFC3 colour composite image of CL J1449+0856. The grey dashed contours represent the X-ray intensity map from Chandra (Valentino et al 2016), while the extended green contours display the SZ signal tracing the mass distribution (Gobat et al 2019). The cyan contours are the 870 μm ALMA sources.…”
Section: Data O B S E Rvat I O N a N D R E D U C T I O Nmentioning
confidence: 99%
“…1) is in a phase of galaxy assembly and star formation quenching that will eventually lead to the creation of the dominant population of massive and passive galaxies that characterizes later galaxy clusters (Strazzullo et al 2016). Unlike the less evolved protoclusters (see Overzier 2016, for a review) that are more commonly found at z ≥ 2, CL J1449+0856 features an extended X-ray emission originating most likely from its hot ICM plasma [as confirmed now by a Sunyaev-Zel'dovich (SZ) detection; Gobat et al 2019] along with an already forming red sequence (Strazzullo et al 2016). The observed X-ray emission is a signature of a dense ICM environment, similar to what is observed in local galaxy clusters.…”
mentioning
confidence: 99%
“…De Breuck et al 2004;Wang et al 2016;Castignani et al 2018;Lee et al 2019). In Coogan et al (2018); Coogan et al (2019), Strazzullo et al (2018) and Gobat et al (2019) we use Atacama Large Millimeter/ submillimeter Array (ALMA) and Karl G. Jansky Very Large Array (VLA) observations to study dust-obscured star-formation, interstellar medium (ISM) content and the intracluster medium (ICM) in Cl J1449+0856. Cl J1449, an X-ray detected galaxy cluster at z = 1.99, is one of the highest redshift mature clusters discovered to date, with the mass of a typical Coma-like progenitor (Gobat et al 2011).…”
Section: J1449 + 0856: a Mature Cluster In The Early Universementioning
confidence: 99%
“…We see a high fraction of cluster galaxies with excited CO (red), and the cluster galaxies lie at enhanced SFE compared to Main Sequence galaxies (green), regardless of their CO excitation. Right: The SZ pressure profile in uv-space of Cl J1449 (white circles, Gobat et al 2019). Red points show the pressure profile if positive galaxy emission is not removed before analysis.…”
Section: Merger-driven Star Formation In the Core Of CL J1449 + 0856mentioning
confidence: 99%
See 1 more Smart Citation